Wave forces on fixed vertical axisymmetric bodies - Dat, Nguyen Tien (Vietnam Journal of Mechanics, 1994)
In this paper, wave forces on fixed vertical axisymmetric bodies are considered by the hybrid boundary element method. A program package on Fortran IV on PC has been developed and applied for the cases of a vertical circular (large and small diameter), step circular cylinder, circular dock, ... The results have been given good agreement with the one obtained by others.